REPRESENTATION OF INDONESIAN CULTURE DIVERSITY IN DJARUM 76 TELEVISION ADVERTISEMENT - Erdita, Dellia; Jamila, Nur Abdina; Rohmawati, Rohmawati (Journal of Language and Literature, 2019)
Cigarette industry is well known in Indonesia, therefore cigarette advertisements are common in television. Although there are regulations regarding cigarette advertisement recently, back in 1990s, cigarette advertisements were frank. The article aims to find out the construction of Indonesian cultural diversity representation in Djarum76 television advertisement. This article uses a qualitative design research method. Constructionist representation by Stuart Hall is used as the analysis approach in this research. The result of this research showed by analyzing 10 iconic scenes and the lyrics of trademark song from Djarum 76 advertisement, the advertisement visually constructs the Indonesian culture diversity, specifically East Java culture. Dominantly, the scenes visualize the iconic places in Indonesia. Therefore, it can be concluded that Djarum 76 wants to be seen as iconic as the cultural places and arts in the television advertisement while subconsciously, Djarum 76 leads the target market to believe in what the lyrics of the advertisement said. Hence, despite we are absorbed with the visual of the advertisement that is showing the beauty of certain places or arts, we also hear the enchanting lyrics which attached in our minds.